2011
DOI: 10.1177/0163443711418272
|View full text |Cite
|
Sign up to set email alerts
|

Women and news: A long and winding road

Abstract: Feminist news researchers have long argued that in the macho culture of most newsrooms, journalists' daily decisions about what is newsworthy remain firmly based on masculine news values. As such, issues and topics traditionally seen to be particularly relevant to women tend to be pushed to the margins of the news where the implicit assumption is that they are less important than those which interest men. In so doing, men's views and voices are privileged over women's, thereby contributing to the ongoing secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
1
18

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(166 citation statements)
references
References 33 publications
11
136
1
18
Order By: Relevance
“…It signals that what they have to say is important. In addition, a direct quote is less likely to be distorted or misreported, even more significant in a press that studies have shown to display sexist tendencies in terms of reporting women (Gill, 2007;Ross and Carter, 2011) and women politicians in particular (Harmer andWring, 2013, O'Neill andSavigny, 2014;Ross and Comrie, 2011;Ross et al, 2013;Van Zoonen, 2006 Male MPs appear in more straightforwardly political stories over each of the years sampled, and on overall average, 11% more often. In contrast, female politicians appear in more stories related to wider society or events, about 14% more often on average.…”
Section: Q2 In All Articles Mentioning Mps What Is the Ratio Of Malmentioning
confidence: 99%
See 1 more Smart Citation
“…It signals that what they have to say is important. In addition, a direct quote is less likely to be distorted or misreported, even more significant in a press that studies have shown to display sexist tendencies in terms of reporting women (Gill, 2007;Ross and Carter, 2011) and women politicians in particular (Harmer andWring, 2013, O'Neill andSavigny, 2014;Ross and Comrie, 2011;Ross et al, 2013;Van Zoonen, 2006 Male MPs appear in more straightforwardly political stories over each of the years sampled, and on overall average, 11% more often. In contrast, female politicians appear in more stories related to wider society or events, about 14% more often on average.…”
Section: Q2 In All Articles Mentioning Mps What Is the Ratio Of Malmentioning
confidence: 99%
“…Research has shown that, in general, there are fewer news items about women's interests or featuring or quoting women as 'experts (Ross and Carter, 2011;Women in Journalism, 2012). Indeed, Howell (2014) has found that the ratio of male to female experts on radio and TV news programmes to be 4:1, a figure that has not changed in two years of monitoring broadcasts.…”
Section: Introductionmentioning
confidence: 99%
“…Prado and Hughes (2009, 7) Concerning the topics covered by reporters, previous studies reveal that hard news is more prestigious than soft ones in the news hierarchy. That is why they are more often relegated to male reporters (North 2014;Ross and Carter 2011;Van Zoonen 1998 and many others). According to Van Zoonen (1998), soft news lack "informational value," for they are not urgent serious topics.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Examining how media uses language and semiotics can reveal how language serves to shape, present, and (re)present lived experiences. Those who serve to monitor language use in media, particularly as it pertains to how gender is portrayed, have found that "media tend to represent reality in ways that most benefit those in positions of power in society in a process of hegemonic reproduction and maintenance of the status quo" (Ross & Carter, 2011, p. 1152. This practice of examining language as a system of power highlights whose voices are heard and whose voices are obscured and just as importantly, what topics are centered (i.e., bathrooms, safety) and what topics are largely silent (resilience, experiences of trans* students of color).…”
Section: Teaching Trans*mentioning
confidence: 99%